Improve Finish Honing of Volume Removal and Surface Roughness with Different Types of Abrasive Material - Gilang Awan; Muhammad Fitri; Adlan Mizan; Muhammad Miftah Rafi; Hasan Anugrah (Politeknik Negeri Jakarta, 2023)
Honing is a method for finishing in manufacturing industries. For the finishing process, a long process would be the challenge. One of the parameters that affected the time of process is volume removal from the surface of the product. The experiment to increase volume removal used several abrasive materials like sandpapers, alumina stone, white alumina stone, and diamond. The quality of the product was determined by the roughness of the surface. The result of this experiment was that the honing process with diamond and white alumina stone had the best volume removal compared to basic honing. The volume removal was raised up to 3 times. The volume removal was 127 mm3/minutes and increased to 344 mm3/minutes for diamond and 382 mm3/minutes for white alumina grinder cup. Quality of surface from honing process with diamond was as good as basic honing with the value of 0.2 µm for basic honing and 0.7 µm for diamond and white alumina has surface roughness much higher than basic honing with the value of 3.2 µm